Evil Dead Center : A Mystery - LaFavor, Carole, 1942-2011 (Book collections on Project MUSE., 2017)
"An Ojibwa woman has been found dead on the outskirts of the Minnesota Red Earth Reservation. The coroner ruled the death a suicide, but after an ex-lover comes back into her life saying foul play was involved, Renee LaRoche wants to prove otherwise. As the events begin to unfold, Renee conducts a presumably normal welfare check on a young Ojibwa boy in foster care. After she learns the boy has suffered abuse, Renee finds herself amid an investigation into the foster care system and the deep trauma it has inflicted on the Ojibwa people. As Renee uncovers horrible truths, she must work through her own childhood issues to help shine a light on the dark web she has stumbled into"--